2019
DOI: 10.1093/ntr/ntz157
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Electronic Cigarette Use and Conventional Cigarette Smoking Is Largely Attributable to Shared Risk Factors

Abstract: Introduction The growing popularity of electronic cigarettes (e-cigarettes) among youth raises concerns about possible causal effects on conventional cigarette smoking. However, past research remains inconclusive due to heavy confounding between cigarette and e-cigarette use. This study uses propensity score methods to robustly adjust for shared risk in estimating the relationship between e-cigarette use and conventional smoking. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 41 publications
1
60
0
Order By: Relevance
“…We rated studies as specific if they adjusted for more than basic demographic factors. In a recent cross-sectional study, accounting for shared risk factors fully explained the relationship between e-cigarette use and current smoking, demonstrating the importance of adjusting for potential confounders such as alcohol and drug use, peer smoking and risk-taking behaviour 33. In addition, some potential confounders, like impulsivity, are difficult to fully capture via self-report and are often assessed relatively crudely.…”
Section: Discussionmentioning
confidence: 99%
“…We rated studies as specific if they adjusted for more than basic demographic factors. In a recent cross-sectional study, accounting for shared risk factors fully explained the relationship between e-cigarette use and current smoking, demonstrating the importance of adjusting for potential confounders such as alcohol and drug use, peer smoking and risk-taking behaviour 33. In addition, some potential confounders, like impulsivity, are difficult to fully capture via self-report and are often assessed relatively crudely.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this paper include the novelty of the counterfactual projections utilized, which offer a valuable contrast to biased analyses [13–15] which dominate this field. Data were taken from sources with large sample sizes and nationally representative weights, producing results generalizable to the US adolescent population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that ECs may have a causal effect on subsequent conventional cigarette smoking among adolescents [11]. Meta‐analyses [11,12] have associated EC use with future cigarette use in adolescents, but methodological research has shown bias in these effect estimates [13–15], motivating novel analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, e-cigarette use among adolescents and/or novice users remains controversial, due to fears of a "gateway" effect whereby e-cigarettes cause youth to become nicotine-dependent and increase their risk of later conventional cigarette smoking (21). However, given recent research supporting a common-liability hypothesis which postulates that the apparent relationship between e-cigarette use and smoking is attributable to a pre-existing liability for nicotine use (23,24), the question of primary prevention becomes relevant (27). That is, for youth who have a propensity to use a nicotine product, it is important to direct them to a less harmful product.…”
Section: Discussionmentioning
confidence: 99%